Penerapan Model Game Based Learning (GBL) Berbasis Wordwall untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa Kelas III Sekolah Dasar Negeri 116/X Lambur II - Upit Hofifah; Mislan Mislan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the beginning, the Natural and Social Sciences (IPAS) Learning Activities in Grade III of Elementary School 116/X Lambur II used a learning model that was not varied, especially still using conventional learning models, so that the learning process in the classroom did not use technology at all. The lack of use of learning models that were less varied, coupled with learning media that only relied on books, made students feel bored and less interested in participating in learning. This research is a Classroom Action Research (CAR) which was carried out in two cycles consisting of planning, implementation, observation and reflection. The subjects in this study were Grade III students of Elementary School 116/X Lambur II. Data analysis techniques: data reduction, data presentation, and conclusions or verification, while data sources: resource persons, documentation, and teaching and learning processes. The results of this study indicate that there is an increase in students' creative thinking skills. Starting from the pre-cycle of learning activities that have not used the Game Based Learning model, student learning outcomes are only 5 out of 20 students who are said to have completed with a percentage of 20% with an average score of 49. Furthermore, from the results of the cycle I action, the minimum score has not been reached, so the study was continued in the cycle II action by making several improvements from the results of the cycle I reflection. From the results of the cycle II action, there was an increase where 18 out of 20 students were declared complete with a percentage of completion of 90% and obtained an overall average score of 85.